2006
DOI: 10.1242/jcs.02984
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of CD21 shedding involves signaling via PKC and indicates the formation of a juxtamembrane stalk

Abstract: Soluble CD21 (sCD21), released from the plasma membrane by proteolytic cleavage (shedding) of its extracellular domain (ectodomain) blocks B cell/follicular dendritic cell interaction and activates monocytes. We show here that both serine- and metalloproteases are involved in CD21 shedding. Using the oxidant pervanadate to mimic B cell receptor activation and thiol antioxidants such as N-acetylcysteine (NAC) and glutathione (GSH) we show that CD21 shedding is a redox-regulated process inducible by oxidation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…CD21 exists also in a soluble form as the receptor can be shed from the plasma membrane by proteolytic cleavage in the short consensus repeat 16 . It has been shown that CD21 is constantly shed from peripheral blood B cells , and that the levels in blood are increased after B cell activation .…”
Section: Introductionmentioning
confidence: 99%
“…CD21 exists also in a soluble form as the receptor can be shed from the plasma membrane by proteolytic cleavage in the short consensus repeat 16 . It has been shown that CD21 is constantly shed from peripheral blood B cells , and that the levels in blood are increased after B cell activation .…”
Section: Introductionmentioning
confidence: 99%
“…ES is known to take place in a constitutive or regulated manner by different stimuli that include: ligand binding, PKC activation [22,60,160,166,203], Ca ++ dynamics [50,72,94,160,166,204], oxidative stress [60,205,206], cell density [24,115,141] and pH [185], and depends upon actin dynamics [207,208], dynamin function [209] or GTPase activation [160,210]. Posttranslational modifications such as glycosilation [38] and extracellular phosphorylation [211], as well as, target molecule structural conformation that preclude accessibility to sheddases [174] are also known to regulate ES (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which this process occurs remains unknown. CD21 shedding is a redox-regulated process involving oxidation of a tyrosine kinase pathway and reduction of metalloproteases [30]. Thus, the possibility remains that ATP-induced reactive oxygen species (ROS) formation may be involved in P2X7-induced CD21 shedding.…”
Section: Cd21 (C3d Receptor)mentioning
confidence: 99%